Fruitful Examination of STEM Education Over Two Decades: Bibliometric Analysis - Putri Amelia Solihah; Ida Kaniawati; Achmad Samsudin; Riandi Riandi (Berkala Ilmiah Pendidikan Fisika, 2024)
This study aims to provide a concise overview of scientific output, prominent researchers, countries, and areas of focus in the field of STEM education research. An examination of the scholarly output in the field of STEM education was conducted using bibliometric methods, focusing on publications published from 2002 to 2023. The methodology employed in this study is a bibliometric analysis technique combined with computational mapping analysis. The tools used are VOSviewer and Rstudio. A total of 25,318 articles were retrieved from the Scopus databases. These papers were published in social sciences, engineering, scientific education, physics, and astronomy journals, among others. The primary results indicate that the number of publications on STEM education has been generally consistent from 2002 to 2023. Co-authorship relationships primarily involve researchers from the same nation. Furthermore, a change in the areas of research focus was noted. Previous research has been extensively conducted in various fields, including the social sciences, engineering, scientific education, physics, and astronomy. A recent study has highlighted the significance of curriculum and curriculum development. In conclusion, research on STEM education still needs to be carried out and developed, especially regarding STEM-based teaching materials.